Differences in health beliefs and behavior compliance of the patients with chronic renal failure - Safitri, Jehan; Seftiana, Miranda; Rusli, Rusdi (Humanitas: Indonesian Psychological Journal, 2022)
Health belief is about a patient’s belief that vulnerability and treatment efficacy can affect health behavior decisions. This research investigated the difference in behavior compliance of patients with chronic renal failure based on gender and health beliefs' contribution to it. The sample of this research was 30 male and 30 female renal failure patients at Brigjend H. Hasan Basry Hospital. Data was collected by behavior compliance scale and health belief scale. Multivariate analysis was used to analyze the data. The results show a significant relationship between male and female patients' health beliefs and behavior compliance. The health belief of male patients is higher than female patients, while the behavior compliance of female patients is higher than males. It can be concluded that health and gender are factors affecting behavior compliance. Therefore, paramedics may increase patients' health beliefs to enhance behavior compliance, especially among female patients with chronic renal failure.